Hydrogen Inhalation Attenuates Oxidative Stress Related Endothelial Cells Injury After Subarachnoid Hemorrhage in Rats - Zhuang, Kai; Zuo, Yu-Chun; Sherchan, Prativa; Wang, Ji-Kai; Yan, Xiao-Xin; Liu, Fei (Frontiers in Neuroscience, 2020)
Background: Subarachnoid hemorrhage (SAH) is a devastating cerebrovascular disease with poor clinical outcome. Nucleotide binding and oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome serves a key role in inflammatory response, which may lead to endothelial cell injury and blood-brain barrier (BBB) disruption. Hydrogen (H2) is considered a neuroprotective antioxidant. This study was set out to explore whether hydrogen inhalation protects against SAH induced endothelial cell injury, BBB disruption, microthrombosis and vasospasm in rats. Methods: One hundred eighty-two male SD rats were used for the study. SAH was induced by endovascular perforation. H2 at a concentration of 3.3% was inhaled beginning at 0.5 hour after SAH for duration of 30, 60 or 120 minutes, followed by single administration or once daily administration for 3 days. The temporal expression of NLRP3 and ASC in the brain was determined, with the effect of hydrogen inhalation evaluated. In addition, brain water content, oxidative stress markers, inflammasome, apoptotic markers, microthrombosis and vasospasm were evaluated at 24 hours or 72 hours after SAH. Results: The expression of NLRP3 and ASC were upregulated after SAH associated with elevated expression of MDA, 8-OHdG, 4-HNE, HO-1, TLR4/NF-κB, inflammatory and apoptotic makers. Hydrogen inhalation reduced the expression of these inflammatory and apoptotic makers in the vessels, brain edema, microthrombi formation and vasospasm in rats with SAH relative to control. Hydrogen inhalation also improved short-term and long-term neurological recovery after SAH. Conclusion: Hydrogen inhalation can ameliorate oxidative stress related endothelial cells injury in the brain and improve neurobehavioral outcomes in rats following SAH. Mechanistically, the above beneficial effects might be related to, at least in part, the inhibition of activation of ROS/NLRP3 axis.